1, 2-(Benz)Azaphospholes: A Slow Beginning to a Bright Future. Issue 1 (2nd January 2020) - Cain, Matthew F.
ABSTRACT: While initially laboratory curiosities, the chemistry of phospholes evolved as a better understanding of their structure, reactivity, and electronic properties was established. With their potential as building blocks for new electronic materials emerging, researchers started to investigate phospholes that maximized π-conjugation. Subsequently, numerous heteroatom-substituted derivatives with a σ 2, λ 3 P-center were reported, but one particular analog, 1, 2-(benz)azaphospholes was noticeably absent, likely due to unusual/impractical synthetic methods. A serendipitous synthetic discovery in 2016 provided straightforward access to these highly aromatic 6π-electron (10π if the fused benzene ring is included) heterocycles. Early reactivity studies have shown that the functionalized products of these rare heterocycles have unusual structures and may find application as catalysts for hydrofunctionalization, as new types of transmetallation agents, or as reactive centers for strong bond activation. GRAPHICAL ABSTRACT: